The papers of John Foster Dulles and of Christian A. Herter, 1953-1961 - Dulles, John Foster, 1888-1959; Herter, Christian Archibald, 1895-1966; Eisenhower, Dwight D. (Dwight David), 1890-1969 (Presidential documents series., 1953)
White House correspondence and memos between Dulles, President Eisenhower and his advisors; memos of conversations with the President; position papers, memos and correspondence of the State Dept.; conversations with Allen Dulles, head of the CIA, dealing with foreign policy and intelligence activities; memos and correspondence on the administration of security; draft and press copy, presidential correspondence, memos, diplomatic notes and aide-memoires, statements and speeches, including inaugural addresses and State of the Union speeches. Herter's papers include memos of record, Cabinet briefing material, classified letters, U-2 white papers and briefing material, White House correspondence, and materials on meetings with the President.